Abrupt shifts in the Indian summer monsoon during the last three millennia. (30th August 2020) - Singh, Shweta; Gupta, Anil K.; Dutt, Som; Bhaumik, Ajoy K.; Anderson, David M.
Abstract: Changes in monsoon precipitation governed agricultural practices and production, health risks, competition and conflict level of preindustrial human societies in South Asia. To understand monsoon shifts and their implication to the South Asian societies, we produced a sub-decadal scale multiproxy record of monsoon variability from the Rewalsar lake, India encompassing the past ~3200 years. Our multi-proxy data from this lake indicate a long, strong Indian monsoon interval during ~1200 BCE to 450 AD with intermittent short-lived dry phases, the latter half is coinciding with the Roman Warm Period. A moderately wet summer monsoon characterizes the Medieval Climate Anomaly during ~950–1300 AD. The Rewalsar lake experienced hypertrophic conditions across the transition from the Medieval Climate Anomaly to the Little Ice Age (~1250 to 1400 AD) marked by severe depletion in δ 15 N ratio (0 to −5‰). The monsoon was weak during the Little Ice Age cold interval and has intensified during the past four centuries in the study region. We find an evidence of the coincidence between increased summer precipitation and economic boom in South Asia with flourishing dynasties during the last three millennia.